Business Analysis Utilization of Gabus Pasir (Butis amboinensis) Waste Fish Meal To Substitution Commercial Fish Meal In Diet on Local Ducks in Hamparan Perak - Syafrina Khuzaimah Lubis (Universitas Sumatera Utara, 2016)
This research was conducted at Deli Serdang from March to June 2015. This study aimed to determine the utilization of Gabus Pasir waste fish meal what can increase the profits of farmers in local ducks laying maintenance business. This survey was conducted at Deli Serdang from March to June 2015. The method used was survey method with consideration of local ducks laying maintenance studies using Gabus Pasir waste fish meal as substitution of fish meal with farm people in the Desa Lama, Hamparan Perak subdistrict Deli Serdang, with the division of business scale. Methods of data collection is by direct observation and interviews to research utilization of Gabus Pasir waste fish meal with the treatments consisting of: commercial fish meal P0 (0% : 10%); P1 (5% : 5%); P2 (10% : 0%), and farmers consisting of 15 farmers. Respondents were categorised into three scales, scale I (100 up to 300 ducks) consists of 13 farmers, scale II (301 up to 501 ducks) consists of 1 farmer and scale III (502 up to 702 ducks) consists of 2 farmers. The results showed that R / C Ratio in research the utilization of Gabus Pasir waste fish meal with treatment P0 (0%: 10%) were 1,19; P1 (5%: 5%) were 1,22; P2 (10%: 0%) were 1,24, while assuming the utilization of 10% Gabus Pasir waste fish meal with crude protein 16% and a production capacity of 60% is not feasible. The conclusion is that the utilization of 10% of Gabus Pasir waste fish meal with crude protein 18% more feasible than the crude protein 16% to increase the income of farmers. Keywords: Business Analysis, Gabus Pasir Waste Fish Meal.